2018
DOI: 10.1007/s11661-018-4520-8
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Recrystallization Mechanisms Governing Texture Development from Rare-Earth Element Additions to Magnesium

Abstract: Unraveling recrystallization mechanisms governing texture development from rare earth element additions to magnesium Pages in Study: 176 Candidate for Degree of Doctor of Philosophy The origin of texture components associated with rare-earth (RE) element additions in wrought magnesium (Mg) alloys is a long-standing problem in magnesium technology. The objective of this research is to identify the mechanisms accountable for rare-earth texture during dynamic recrystallization (DRX). Towards this end, we designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 132 publications
0
20
0
Order By: Relevance
“…[251] The addition of non-RE alloying elements to the Mg-RE alloys does not seem to affect the RE textures, when the major and minor alloying elements are all in low concentrations. A microstructural study made by Imandoust and co-workers [253] of Mg-Y alloys containing various amounts of Zn, Al, and Mn revealed that the RE textures were preserved when the alloys were extruded at 450°C and 40 mm min À1 speed and 6:1 extrusion ratio. Depending on the specific alloy composition, the microstructure also had other texture components such as 10 10 // ED and [0001] // ED.…”
Section: Polycrystalline Extrusionsmentioning
confidence: 99%
“…[251] The addition of non-RE alloying elements to the Mg-RE alloys does not seem to affect the RE textures, when the major and minor alloying elements are all in low concentrations. A microstructural study made by Imandoust and co-workers [253] of Mg-Y alloys containing various amounts of Zn, Al, and Mn revealed that the RE textures were preserved when the alloys were extruded at 450°C and 40 mm min À1 speed and 6:1 extrusion ratio. Depending on the specific alloy composition, the microstructure also had other texture components such as 10 10 // ED and [0001] // ED.…”
Section: Polycrystalline Extrusionsmentioning
confidence: 99%
“… 16 studied the effect of RE element on the recrystallization textures in Mg-Ce and Mg-Gd binary alloys and reported that CDRX facilitated the transformation of a sharp <10 0> basal fiber texture into a randomized texture. In contrast, their following study 17 in the extruded Mg-Zn-Al-Y-MM (MM: Mischmetal) alloys revealed that CDRX sharpened the <10 0> basal fiber texture and DDRX was shown to be the predominant mechanism for texture modification. Despite these efforts, there are still some differences of views on the DRX behavior in dilute Mg-RE alloys during extrusion and its corresponding contribution to the texture development.…”
Section: Introductionmentioning
confidence: 94%
“…Some recent studies have already been devoted to the issue on the correlation with DRX and formation of RE texture in dilute Mg-RE extrusions 13 17 . Hadorn et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additions of rare earth elements proved to be useful for improving formability at low temperature, primarily by means of texture weakening. However, energy absorption levels remained shockingly low under high rate regimes relevant to car crash deformation [ 4 , 5 ]. In order to expand the range of industrial applications of Mg alloys the way twinning affects hardening must be better understood and predicted.…”
Section: Introductionmentioning
confidence: 99%